Clopidogrel Resistance in Patients with Coronary Stent Thrombosis - Dyah Wulan Anggrahini; Bambang Irawan (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2015)
Antiplatelet drugs plays important role in the therapy of atherothrombosis. Dual antiplatelet therapy is recommended as a strategy for the prevention of stent thrombosis in patients who underwent Percutaneus Coronary Intervention (PCI). In combination with aspirin, tienoperidine is currently the drug of choice to prevent stent thrombosis. The issue of the high inter-individual variability ofresponse is clinically relevant, since poor responders are not adequately protected from major adverse cardiac events (MACE). We reported a 62-years old woman underwent primary PCI with implantation of BAS. She was later known to have in-stent thrombosis in the LAD after repeated angiography. The probable cause for the later cardiac event in this patient were overlapped stent, small vessel diameter, diabetes mellitus, and the patients also shown a persistent platelet reactivity despite clopidogrel therapy. We administered this patient with pasugrel as antiplatelet replacing clopidogrel and the patient was managed without ischemic symptoms afterwards.